Expert systems for the planning and management of personnel training in public institutions in the city of Esmeraldas (Revista Científica Interdisciplinaria Investigación y Saberes, 2025)
This study focuses on developing a theoretical-practical framework for the implementation of an expert system for the planning and management of personnel training in public institutions in the city of Esmeraldas. The main objective is to analyze and systematize existing information on expert systems to optimize human talent management. The methodology used was based on an exhaustive documentary review, evaluating the current literature on training needs, knowledge representation techniques and the inclusion of explanation modules in expert systems. The results indicate that expert systems can significantly improve the efficiency of training planning, ensuring that staff competencies are aligned with organizational objectives. Notable findings of the study include the need for a pre-functional manual system, the integration of advanced knowledge representation techniques, and the validation of prototypes using qualitative methods. This approach not only optimizes training resources, but also increases staff performance and satisfaction, contributing to the socioeconomic development of Esmeraldas.